2020
DOI: 10.21203/rs.3.rs-27032/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes, social responsibilities and  career plans toward Corona Virus Disease 2019 (Covid-19)  among Chinese clinical medical students

Abstract: Purpose: To assess knowledge, attitudes and social responsibilities toward Covid-19 among Chinese clinical medical students. Method: Self-administered questionnaires were used to collect data for 889 clinical medical students from 3 well-known Chinese medical universities. The questionnaire was comprised of three domains which consisted of 7 items for knowledge, 5 items for attitudes and social responsibilities and 4 items for career planning. Results: It was found that 47.2%, 46.9% of the clinical medical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In China, medical resources are unevenly distributed, such as resources of equipment and talents, and are mainly concentrated in developed cities and high-level hospitals (37). We considered the medical curiosity as the main cause of the significant difference in the knowledge toward COVID-19 between the participants from tertiary and basic-level hospitals, which has been reported in recent studies (38,39). Interestingly, studies of educational psychology revealed that the trait of curiosity is positively associated with academic achievement and the educational process may affect the state of curiosity of medical students (40).…”
Section: Discussionmentioning
confidence: 99%
“…In China, medical resources are unevenly distributed, such as resources of equipment and talents, and are mainly concentrated in developed cities and high-level hospitals (37). We considered the medical curiosity as the main cause of the significant difference in the knowledge toward COVID-19 between the participants from tertiary and basic-level hospitals, which has been reported in recent studies (38,39). Interestingly, studies of educational psychology revealed that the trait of curiosity is positively associated with academic achievement and the educational process may affect the state of curiosity of medical students (40).…”
Section: Discussionmentioning
confidence: 99%